The courage to act a memoir of a crisis and its aftermath - Bernanke, Ben 1953- (Norton, 2015)
The former chairman of the Federal Reserve documents his rise from a Southern youth to Ivy League professorships prior to the 2007 housing bubble burst, detailing the dramatic efforts to salvage the U.S. economy that made him "Time" magazine's 2009 Person of the Year